2018
DOI: 10.1016/j.oraloncology.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab vs investigator’s choice in recurrent or metastatic squamous cell carcinoma of the head and neck: 2-year long-term survival update of CheckMate 141 with analyses by tumor PD-L1 expression

Abstract: Nivolumab significantly improved OS at the primary analysis and demonstrated prolonged OS benefit vs IC and maintenance of a manageable and consistent safety profile with 2-year follow-up. OS benefit was observed with nivolumab irrespective of PD-L1 expression and HPV status. (Clinicaltrials.gov: NCT02105636).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
533
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 649 publications
(573 citation statements)
references
References 12 publications
28
533
0
12
Order By: Relevance
“…Importantly, infiltration of PD1 + T‐cells into HPV‐positive tumors was associated with favorable prognosis . More recently clinical trials have shown that immune checkpoint blockade significantly improves survival over standard therapy in recurrent HNSCC, including HPV‐OPC . These insights suggest that surrogates of a diminished immune response to tumor, such as TIL depletion, may predict poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, infiltration of PD1 + T‐cells into HPV‐positive tumors was associated with favorable prognosis . More recently clinical trials have shown that immune checkpoint blockade significantly improves survival over standard therapy in recurrent HNSCC, including HPV‐OPC . These insights suggest that surrogates of a diminished immune response to tumor, such as TIL depletion, may predict poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These percentages were then further divided into several categories: <1%, 1–4%, 5–24%, 25–49%, and ≥50%. As the threshold for PD‐L1 immunopositivity in SDCs has not yet been established, PD‐L1 immunopositivity was determined according to the criteria established in the KEYNOTE 012, Checkmate 141 and MEDI4736 trials for HNSCC . These criteria are: (i) a combined positive score (CPS) (calculated as the sum of positive TCs and positive ICs divided by the total TCs multiplied by 100) of at least 1; (ii) ≥1% of TCs stained; and (iii) ≥25% of TCs stained .…”
Section: Methodsmentioning
confidence: 99%
“…The use of checkpoint inhibitors in the management of patients with head and neck squamous cell carcinoma (HNSCC) has become increasingly common following successful early clinical trials. Additionally, it has been shown that blockade of programmed death‐1 (PD‐1) and/or programmed death ligand‐1 (PD‐L1) has positive therapeutic benefits in HNSCC patients . Moreover, PD‐1 and PD‐L1 have emerged as the key checkpoints that can be manipulated with inhibitory monoclonal antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…pembrolizumab and nivolumab) have been proved to be safe and effective [27,28,29]. Furthermore, the phase III randomized KEYNOTE-040 trial testing the efficacy of pembrolizumab versus standard treatment (methotrexate, docetaxel or cetuximab) is ongoing (ClinicalTrials.gov Identifier NCT02252042).…”
Section: Discussionmentioning
confidence: 99%
“…Modern agents (i.e. PD-1-receptor antibodies) have been proved to be safe and effective in patients with recurrent or metastatic SCCHN [27,28,29]. …”
Section: Introductionmentioning
confidence: 99%